Effect of Pressure Wound Dressing Using Elastic Bandage Following Axillary Dissection Compared to Standard Wound Dressing on Postoperative Seroma Development and Surgical Complications - Acar, Kadriye; Yılmaz Bozok, Yeliz (The European Research Journal, 2026)
Objectives: Postoperative seroma is a common complication following breast surgery and axillary dissection. This issue persists despite attempts to prevent seroma, including intraoperative fibrin isolation, application of thrombin spray, fascia treatment techniques, and shoulder immobilization. This study aims to evaluate the impact of pressure wound dressings on the development of postoperative seroma after axillary dissection. Methods: This is a randomized, controlled prospective study involving 63 patients. Pressure wound dressings were applied to patients in the intervention group (n=32), while standard dressings were applied to those in the control group (n=31). Both groups were compared regarding the postoperative length of stay for the drain catheter, the amount of drainage, duration of hospital stay, postoperative pain levels on the 1st, 3rd, and 10th days, as well as rates of reoperation and rehospitalization. Results: The study indicated that the daily and total fluid drainage was significantly lower in the pressure wound dressing group. Moreover, postoperative pain scores on the 1st, 3rd, and 10th days, as well as the duration of hospital stay for patients after surgery, were notably lower in this group. Conclusions: The use of pressure wound dressings significantly reduces fluid drainage and postoperative pain in patients undergoing axillary dissection. This approach holds promise for decreasing postoperative complications.